2014
DOI: 10.1016/j.polymdegradstab.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Disulfides – Effective radical generators for flame retardancy of polypropylene

Abstract: The potential of thirteen aliphatic, aromatic, thiuram and heterocyclic substituted organic disulfide derivatives of the general formula R-S-S-R' as a new group of halogen-free flame retardants (FR) for polypropylene films have been investigated. According to DIN 4102-1 standard ignitibility test, for the first time it has been demonstrated that many of the disulfides alone can effectively provide flame retardancy and self-extinguishing properties to polypropylene (PP) films at already very low concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 39 publications
3
39
1
Order By: Relevance
“…The incorporation of 5 wt% of compound 1 , increased the LOI value from 18.4±0.15 O 2 % to 20.0±0.23 O 2 % , whereas the addition of 10 wt% of melem increased the LOI value of PP by only 19.1±0.30 O 2 % . The LOI values observed for compound 1 were similar to those reported for DTBB in PP, which rises from 17.0 O 2 % to 19.8 O 2 % (0.5 wt.% DTBB), 20.6 O 2 % (1 wt.% DTBB), 20.3 O 2 % (3 wt.% DTBB), 20.4 O 2 % (5 wt.% DTBB), and 20.4 O 2 % (10 wt.% DTBB) . According to these results, compound 1 shows flame‐retardant effects, but further investigations are required and are currently being performed.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The incorporation of 5 wt% of compound 1 , increased the LOI value from 18.4±0.15 O 2 % to 20.0±0.23 O 2 % , whereas the addition of 10 wt% of melem increased the LOI value of PP by only 19.1±0.30 O 2 % . The LOI values observed for compound 1 were similar to those reported for DTBB in PP, which rises from 17.0 O 2 % to 19.8 O 2 % (0.5 wt.% DTBB), 20.6 O 2 % (1 wt.% DTBB), 20.3 O 2 % (3 wt.% DTBB), 20.4 O 2 % (5 wt.% DTBB), and 20.4 O 2 % (10 wt.% DTBB) . According to these results, compound 1 shows flame‐retardant effects, but further investigations are required and are currently being performed.…”
Section: Resultssupporting
confidence: 83%
“…Wilen et al. showed that radical generators based on alkyl disulfides (structure type: R−S−S−R) had promising flame‐retardant properties in polypropylene (PP) . Furthermore, the flame retardancy of such disulfides was proved by Döring et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are few reports on the use of sulfur as flame retardant in some polymers [51,52], there is seldom report about polyphosphoramide containing sulfur flame retardant epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide bonds connecting two s‐triazine rings have also been reported . However, this bond type is not the subject of our present study.…”
Section: Introductionmentioning
confidence: 96%
“…In a previous paper, we presented the first representatives of a new class of arylthio‐substituted s‐heptazines . Arylthiocyamelurates are able to release thiyl radicals during thermal decomposition, and thiyl radicals are known to be a species with flame‐retardant effects . Our model arylthio‐substituted s‐heptazine molecule, triphenylthiocyamelurate (C 6 H 5 S) 3 C 6 N 7 , decomposes thermally at around 393 °C .…”
Section: Introductionmentioning
confidence: 99%